Unleashing 5G Seamless Integration With TSN for Industry 5.0: Frame Forwarding and QoS Treatment - Oscar Adamuz-Hinojosa; Felix Delgado-Ferro; Jorge Navarro-Ortiz; Pablo Munoz; Pablo Ameigeiras (IEEE Open Journal of the Communications Society)
Integrating Time-Sensitive Networking (TSN) and 5th Generation (5G) systems is key for providing wireless low-latency services in industry. Despite research efforts, challenges remain. Due to the lack of commercial 5G modems supporting Ethernet-based sessions, tunneling mechanisms must be used to enable Layer 2 connectivity between TSN islands via IP-based 5G modems. Furthermore, harmonizing traffic classification and prioritization between TSN and 5G technologies is crucial for meeting industrial service requirements. In this work, we propose a Virtual Extensible LAN (VxLAN)-based solution to harmonize frame forwarding and Quality of Service (QoS) treatment among 5G and TSN. Our solution supports multiple Virtual Local Area Networks (VLANs) across several production lines. Furthermore, it supports TSN traffic mapping into 5G QoS flows. We use a 5G testbed to validate the effectiveness of the adopted solution. Our results show the average delay introduced by the proposed mechanisms is approximately $100~μ s$ , which is significantly lower than the typical 5G packet transmission delay. Moreover, our findings demonstrate our solution preserves QoS treatment between the 5G system and TSN, ensuring that the priority of 5G QoS flows aligns with the priorities of industrial traffic flows.